Explanation:
To find the maxima/minima of a function, we solve for the derivative of the given function
![g(x) = (x^2 - 3x + 4)/(x^2 + 3x + 4)](https://img.qammunity.org/2022/formulas/mathematics/college/c85byjm9ijhy4qz4irjztlwtu5ljfbaqnf.png)
Recall that according to the quotient rule of differentiation, if a function g(x) is defined as a ratio of two functions f(x) and h(x), then the derivative of g(x) is
![g'(x) = (f'(x)h(x) - f(x)h'(x))/([g(x)]^2)](https://img.qammunity.org/2022/formulas/mathematics/college/kh98k76tyviingqi7flxc6i4sp11kqh3z9.png)
Let
![f(x) = x^2 - 3x + 4 \Rightarrow f'(x) = 2x - 3](https://img.qammunity.org/2022/formulas/mathematics/college/n9xm0jt8z5u9ajvdeygrufn0niuv8ldm69.png)
![h(x) = x^2 + 3x + 4 \Rightarrow g'(x) = 2x + 3](https://img.qammunity.org/2022/formulas/mathematics/college/y4vmcijt45to46axutw5qp0fp57o7sfl8t.png)
The derivative g')x) is then
![g'(x) = ((2x - 3)(x^2 + 3x + 4) - (2x + 3)(x^2 - 3x + 4))/((x^2 + 3x + 4)^2)](https://img.qammunity.org/2022/formulas/mathematics/college/hptrj5nyvsq35xc47se24rfor19oyl9q8w.png)
Carrying out the multiplication and collecting all similar terms, we arrive at
![g'(x) = (6(x^2 - 4))/((x^2 + 3x + 4)^2)](https://img.qammunity.org/2022/formulas/mathematics/college/cflybr4w3dgvv8ql1nmswybbsbzbshlywd.png)
The maxima/minima of the function g(x) occurs where g'(x) = 0 and this happens when the numerator of g'(x) is
![x^2 - 4 = 0 \Rightarrow x = \pm2](https://img.qammunity.org/2022/formulas/mathematics/college/kijs42q9phhc8crel8pk9hemjntep6dyke.png)
Look at the graph above. The blue line represents the function g(x) and the red line is for the derivative of g(x) and you can clearly see that maxima/minima occurs when the red line intersects the horizontal axis, i.e., becomes zero at
![x = \pm2.](https://img.qammunity.org/2022/formulas/mathematics/college/gjkdtu1cfgncqo2wz0yf4gcaaj6dl12fvn.png)